SARS-CoV-2 infection and transmission in primary schools in England in June–December, 2020 (sKIDs): an active, prospective surveillance study. (June 2021) - Ladhani, Shamez N; Baawuah, Frances; Beckmann, Joanne; Okike, Ifeanichukwu O; Ahmad, Shazaad; Garstang, Joanna; Brent, Andrew J; Brent, Bernadette; Walker, Jemma; Andrews, Nick; Ireland, Georgina; Aiano, Felicity; et al.
Summary: Background: Little is known about the risk of SARS-CoV-2 infection and transmission in educational settings. Public Health England initiated a study, COVID-19 Surveillance in School KIDs (sKIDs), in primary schools when they partially reopened from June 1, 2020, after the first national lockdown in England to estimate the incidence of symptomatic and asymptomatic SARS-CoV-2 infection, seroprevalence, and seroconversion in staff and students. Methods: sKIDs, an active, prospective, surveillance study, included two groups: the weekly swabbing group and the blood sampling group. The swabbing group underwent weekly nasal swabs for at least 4 weeks after partial school reopening during the summer half-term (June to mid-July, 2020). The blood sampling group additionally underwent blood sampling for serum SARS-CoV-2 antibodies to measure previous infection at the beginning (June 1–19, 2020) and end (July 3–23, 2020) of the summer half-term, and, after full reopening in September, 2020, and at the end of the autumn term (Nov 23–Dec 18, 2020). We tested for predictors of SARS-CoV-2 antibody positivity using logistic regression. We calculated antibody seroconversion rates for participants who were seronegative in the first round and were tested in at least two rounds. Findings: During the summer half-term, 11 966 participants (6727 students, 4628 staff, and 611 with unknown staff or student status) in 131 schools had 40 501 swabs taken. Weekly SARS-CoV-2 infection rates were 4·1 (one of 24 463; 95% CI 0·1–21·8) per 100 000 students and 12·5 (two of 16 038; 1·5–45·0) per 100 000 staff. At recruitment, in 45 schools, 91 (11·2%; 95% CI 7·9–15·1) of 816 students and 209 (15·1%; 11·9–18·9) of 1381 staff members were positive for SARS-CoV-2 antibodies, similar to local community seroprevalence. Seropositivity was not associated with school attendance during lockdown (p=0·13 for students and p=0·20 for staff) or staff contact with students (p=0·37). At the end of the summer half-term, 603 (73·9%) of 816 students and 1015 (73·5%) of 1381 staff members were still participating in the surveillance, and five (four students, one staff member) seroconverted. By December, 2020, 55 (5·1%; 95% CI 3·8–6·5) of 1085 participants who were seronegative at recruitment (in June, 2020) had seroconverted, including 19 (5·6%; 3·4–8·6) of 340 students and 36 (4·8%; 3·4–6·6) of 745 staff members (p=0·60). Interpretation: In England, SARS-CoV-2 infection rates were low in primary schools following their partial and full reopening in June and September, 2020. Funding: UK Department of Health and Social Care.